Bumblebees depend on ericaceous species to survive in temperate heathlands. Issue 1 (27th October 2016) - Moquet, Laura; Vanderplanck, Maryse; Moerman, Romain; Quinet, Muriel; Roger, Nathalie; Michez, Denis; Jacquemart, Anne‐Laure
Abstract: Bumblebees are the predominant wild pollinators for many plant species in temperate regions. A bumblebee colony requires pollen and nectar throughout its lifetime, but degraded and fragmented habitats may have gaps in the temporal and spatial continuity of floral resources. Heathlands are open biotopes that provide favourable habitat for bumblebees like Bombus jonellus, a declining species in Belgium. In heathlands, ericaceous species are the main plants that provide pollen and nectar for bumblebees. Although the nectar composition of ericaceous species has been previously studied, data on pollen composition remain scarce. We examined bumblebee diets (composition of their pollen loads) in Belgian heathlands over the course of a colony lifetime to assess the fidelity of bumblebees for ericaceous species. We compared nutritional values by investigating the chemical composition (amino acids, polypeptides and sterols) of the pollen of the ericaceous and dominant non‐ericaceous species present in pollen loads. No relationship was detected between the abundance of a particular plant species in bumblebee loads and its pollen composition. The successive flowering periods and the nutritional quality of pollen of ericaceous species offer valuable resources for bumblebees. Ericaceous species represent a large part of bumblebee diets in heathlands, especially in early spring and late summer when the diversity of other flowering species was low. Bumblebee pollen loads also contained non‐ericaceous flowering species that grow outside heathlands. Thus, land planning must incorporate conservation strategies for the different elements of the landscape matrix, including heathlands, peatlands, meadows and margins.